Selecting Infants With Cryptorchidism and High Risk of Infertility for Optional Adjuvant Hormonal Therapy and Cryopreservation of Germ Cells: Experience From a Pilot Study - Thorup, Jorgen; Clasen-Linde, Erik; Dong, Lihua; Hildorf, Simone; Kristensen, Stine Gry; Andersen, Claus Yding; Cortes, Dina (Frontiers in Endocrinology, 2018)
Introduction Orchiopexy for congenital cryptorchid testes is recommended between ½ and 1 year of age to preserve testicular germ cell maturation. Early operation is not enough to preserve fertility in 22 and 36% of cases. Aim of this study was to set up a protocol for optional adjuvant hormonal therapy after orchiopexy and thereafter cryopreservation of testicular biopsies from infants with bilateral cryptorchidism and high infertility risk. Materials and methods We included 17 boys with bilateral cryptorchidism, normal FSH, and impaired germ cell number per tubular transverse section (G/T) in testicular biopsies at orchiopexy, 7 months to 3½ years old. Postoperatively, optional adjuvant LHRH (kryptocur®) 0.2 mg/0.1 mL 2× every second day in 16 weeks were offered. Ten boys were applicable for age matching according to parent’s choice of treatment regime and G/T. Five of them had kryptocur®, and five were controls. Repeat bilateral testicular biopsy evaluation and cryopreservation were offered to all boys 12 months after primary orchiopexy. For cryopreservation, tissue pieces were incubated with a cryoprotectant with a slow program freezing. Results Two out of five kryptorcur®-treated boys normalized both the average G/T and the number of adult dark spermatogonia (Ad-S). Another kryptocur®-treated boy with initial low G/T and no Ad-S increased the G/T and achieved normal number of Ad-S at time of cryopreservation. In the control group, two patients reached only normal lower range regarding the G/T and the number of Ad-S. None of boys with less than average 0.2 G/T improved significantly, whether they were kryptocur®-treated or not. Conclusion Based on literature and the present results, we recommend adjuvant LHRH treatment to boys with cryptorchidism and insufficient genuine gonadotropin stimulation at time of surgery, as these patients have high infertility risk. Cryopreservation should be an option in case of treatment failure of adjuvant LHRH. However, to avoid repeat surgery with biopsy, some parents may choose biopsy for cryopreservation at time of the initial bilateral orchiopexy, well informed that the procedure may only be truly indicated in 22 and 36% of the cases.